ANALISIS SISTEM INFORMASI MANAJEMEN UNTUK PENINGKATAN PRODUKTIVITAS UMKM DENGAN PENDEKATAN GAMIFIKASI - Nazwa Riwanda; Muhammad Irwan Padli Nasution (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
Top-level company managers need external information for strategic policies, while middle or lower managers need internal operational information. Management Information Systems (MIS) need to be balanced between human resources with IT knowledge and funds for sophisticated computer equipment. SIM integration and gamification help MSMEs manage resources and identify real-time problems. Ecommerce plays a role in helping MSMEs in online trading. MSMEs in Indonesia face capital, management, marketing and competitiveness challenges. Information technology supports decision making and transaction integration with organizational strategy. The research method used is descriptive qualitative with analysis to explain the phenomenon in depth and detail. Research focuses on the process and meaning of the subject with a theoretical basis as a guide. The use of various sources such as books and journals also supports the quality of research.